Algunas notas a considerar en el análisis monetario de los ciclos económicos - Rivas Santos, Pablo (2013)
This article describes the monetary explanations of business cycles, considering that credit expansion occurs through excessive monetary base and hence excessive bank lending. The obstacles encountered by the monetary explanation of the cyclical crises are theoretical and political. The constant ups and downs of economic activity, and the inevitable sequence of booms and busts, are effects caused by repeated attempts to reduce the interest by credit expansion. Inevitably the final collapse of the boom generated by credit expansion. One can only cause soon choose between ending the crisis credit expansion, or let the monetary system crisis occurs a little later. On the monetary explanation of economic cycles and banks BCR considered pernicious interest level determined by the market, so it should cause a reduction of interest by credit expansion. This measure will lead to economic cycles. Thus, the 1992-2012 period reflected a continued economic progress and again interrupted by booms and busts. The statistics reflect these fluctuations contrary to the general trend toward a continued increase in investment and a constant increase in production.